Peran Semantik dalam Menafsirkan Nilai Budaya yang Terkandung dalam Upacara Tabuik di Pariaman Sumatera Barat - Rahmatunissa Rahmatunissa; Sophia Rahmawati (Haluan Sastra Budaya, 2025)
This article discusses the role of semantics in interpreting the cultural values embedded in the Tabuik ceremony in Pariaman, West Sumatra. The study employs a descriptive qualitative approach through direct observation and in-depth interviews with Pak Arif, a 50-year-old local resident who has actively participated in the Tabuik ceremony since his youth. Observations reveal that elements of the Tabuik, such as the buraq,bungosalapan, and tonggak atam, carry strong symbolic meanings. For instance, the buraq is understood as a symbol of spiritual strength and hope, while bungo salapan reflects the values of unity and the interconnectedness between local customs and Islamic teachings. These symbols are not merely ornamental; they serve as conveyors of cultural messages passed down through generations. A semantic analysis of these symbols helps clarify how the community understands and preserves the values embedded in their traditions. Thus, cultural semantics becomes an essential tool for maintaining identity, strengthening social solidarity, and reviving the meaning contained within local traditions such as the Tabuik.